Expressão gênica e viabilidade de folículos pré-antrais inclusos em fragmentos de córtex ovarianos cultivados in vitro de macaco-prego (Sapajus apella) - BRITO, Adriel Behn de (Universidade Federal do Pará, 2014)
The aim of the present study was to investigate the stability of three reference genes in the ovarian tissue of capuchin monkeys (Sapajus apella) and to develop a short-term in vitro culture system for the activation and growth of preantral follicles from capuchin monkeys. To this end two experiment were conducted as follow. Experiment I: Fresh and cryoprotectant exposed ovarian biopsies were used. Both fresh and exposed ovarian tissues were subjected to total RNA extraction and synthesis of cDNA. After amplification of cDNA by real-time PCR, the GeNorm, Bestkeeper and Normfinder software were used to evaluate the stability of glyceraldehyde-2-phosphate dehydrogenase (GAPDH), hypoxanthine phosphoribosyltransferase 1 (HPRT1) and TATA-binding protein (TBP). Experiment II: Ovarian tissue from four healthy mature females were collected and divided into nine ovarian cortical pieces of 1 mm³. One ovarian fragment (control) was immediately divided in two pieces, which were subjected to viability analysis or qRT-PCR. The remaining 8 fragments were individually cultured in vitro in a medium consisting of TCM supplemented with 100 ng/mL EGF (T1), either or not added with 10 μM BME (T2), 100 ng/mL BMP4 (T3), 25 IU PMSG (T4), 10 μM BME and 100 ng/mL BMP4 (T5), 10 μM BME, 25 IU PMSG (T6), 100 ng/mL BMP4, 25 IU PMSG (T7) or 10 μM BME, 100 ng/mL BMP4, 25 IU PMSG (T8). Results demonstrated that, in the ovarian tissue from capuchin monkeys, HPRT1 and TBP were the most suitable reference genes and thus could be used as parameters to normalize data in future studies. In contrast, GAPDH appeared as the least stable gene among the tested reference genes. After in vitro culture, all treatments resulted in similar percentages of viable preantral follicles. Ovarian tissue cultured in the presence of EGF + BME/BMP4/PMSG resulted in an increased rate of follicular activation and growth, as well as in the up regulation of AMH, BMP15 and GDF9, specific markers of follicular development. In conclusion, HPRT1 and TBP are the most stable reference genes in fresh and cryoprotectant exposed ovarian tissue from capuchin monkeys. Preantral follicles are able to develop in vitro when cultured in a medium supplemented with PMSG, BME and BMP4. Follicular viability, however, was maintained independently on the culture medium. The use of growth factors as markers of follicular development was crucial to identify the best culture medium.